Effectiveness of programme for reducing cardiovascular risk for men in one general practice. Issue 6893 (19th June 1993) - Gibbins, R L; Riley, M; Brimble, P
Abstract : OBJECTIVES--To assess the effectiveness of a programme for reducing cardiovascular risk in men in terms of clinical measurements and perceptions of patients. DESIGN--Collection of paired data on men attending well person clinics over three to five years. Questionnaire to determine changes in risk related habits. SETTING--Well person clinics in rural general practice with five partners in mid-Wales. SUBJECTS--The first 687 men seen in the clinic: analysable data obtained on 520. Initial age range 28-60 years. MAIN OUTCOME MEASURES--Analysis of serum cholesterol concentration (mmol/l) and blood pressure (mm Hg). Changes in diet, exercise, smoking, and drinking. RESULTS--Mean (SD) cholesterol concentration for all subjects increased from 5.8 (1.0) to 6.0 (1.0), p < 0.001. Overall percentage of ideal weight and mean systolic blood pressure also increased. Mean diastolic blood pressure was unchanged at 84 mm Hg. Professed dietary change, age, and number of visits all had significant effects on final cholesterol concentration. Those seen more often showed a significant decrease in cholesterol concentrations (in those seen more than twice mean (SD) initial value 6.7 (0.9) mmol/l v final value 6.5 (1.0) mmol/l, p < 0.001). Those over 45 years at start of study showed a significant decrease in diastolic blood pressure (mean (SD) initial value 89 (9) mm Hg v final value 86 (7) mm Hg, p < 0.001). CONCLUSIONS--These clinics are not effective in achieving a reduction in mean cholesterol concentration or blood pressure, despite evidence that the message of reduction in risk had been successfully transmitted. Success was achieved in older patients and those in whom a definite problem was identified. Identification of high risk groups and clinical case finding with appropriate long term follow up may be more cost effective in reducing cardiovascular risk than non-specific screening of the whole population.